Hydrogel constructed based on mechanical interlocking principle and preparation method thereof

By adopting the mechanical interlocking principle in hydrogel materials and using a combination of flexible polymer backbones and rigid short side chains to build a network structure, the problem of insufficient crack growth resistance of existing hydrogel materials is solved and high strength is achieved. , high toughness and excellent resistance to crack growth.

CN119331182AActive Publication Date: 2025-01-21NANJING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411501595.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing hydrogel materials have shortcomings in crack growth resistance and are difficult to withstand large-scale deformation, which limits their use in applications such as flexible electronic devices.

Method used

The water gel material based on the principle of mechanical interoperability is adopted, and its network structure is combined with a combination of flexible polymer main chain and rigid short -sided chain to form a mechanical interoperability structure to achieve the balance between disproportion and mechanical interoperability.

Benefits of technology

The high strength, high toughness, and high -resistant crack growth performance of hydraulic gel materials have been achieved. The amount of Yang's mold reaches 23kPa, the breakthrough strength reaches 3.1MPa, the toughness reaches 28mj/m3, the fracture toughness reaches 57kj/m2, which is 4 times more than the rubber of the rubber. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses hydrogel constructed on the basis of a mechanical interlocking principle as well as a preparation method and application of the hydrogel. The hydrogel consists of a flexible macromolecular main chain and a rigid short side chain, wherein a flexible macromolecular main chain is wound as a main body, and a rigid short side chain is added into the flexible macromolecular main chain as a mechanical interlocking component unit. The super-strong, super-tough and crack-growth-resistant hydrogel material based on the mechanical interlocking structure can be applied to repair and regeneration of soft robots, artificial skin, flexible electronic devices, artificial tendons and cartilages. The single end of the rigid polypeptide is connected with acrylic acid to provide unsaturated carbon-carbon double bonds participating in copolymerization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new materials, and in particular to a super-strong, super-tough, crack growth-resistant hydrogel material and a preparation method and application thereof. Background Art

[0002] The cross-linking methods of conventional hydrogels are mainly divided into physical cross-linking and chemical cross-linking. Physical cross-linking mainly includes protein-specific interactions, hydrogen bonds, ionic interactions, hydrophobic interactions, metal coordination, etc. These cross-linking methods are mainly used to prepare injectable hydrogels or increase the dissipation of hydrogels. On the other hand, compared with physical cross-linking, chemically cross-linked hydrogels usually have higher elasticity and toughness due to the higher bond energy of covalent bonds, but due to the irreversibility of covalent bond destruction, most chemically cross-linked hydrogels are difficult to withstand large-scale deformations. This disadvantage limits its application in flexible electronic devices and other materials that require large-scale deformation.

[0003] The present invention proposes a hydrogel based on a mechanically interlocked structure of polymer chains. Unlike physical or chemical crosslinking, mechanically interlocked hydrogels do not have strictly defined crosslinking points, but are the result of a competitive balance between mechanical interlocking and swelling forces. Since the mechanically interlocked hydrogel is integrally crosslinked, it is very insensitive to defects and has almost the same fracture strain as a crack-free hydrogel when it has a crack of 30% of its original width. Its Young's modulus reaches 23 kPa, its fracture strength reaches 3.1 MPa, and its toughness reaches 28 MJ / m 3 , fracture toughness reaches 57kJ / m 2 , and the fracture toughness is about 4 times that of rubber. The design of mechanical interlocking hydrogels provides a different approach from the traditional hydrogel cross-linking method. Due to their unique structure and excellent mechanical properties, these hydrogels can be used in soft robots, artificial skin, artificial tendons, and cartilage repair. Summary of the invention

[0004] The problem to be solved by the present invention is to propose an innovative solution to the shortcomings of the above-mentioned existing materials, namely, the lack of crack growth resistance in hydrogel materials, and to construct a hydrogel material with high strength, high toughness and high crack growth resistance.

[0005] To solve the above problems, the solution adopted by the present invention is as follows: A hydrogel constructed based on the principle of mechanical interlocking, characterized in that the hydrogel network is mainly composed of a flexible polymer main chain, and rigid short side chains are added to the flexible polymer main chain as mechanical interlocking constituent units. During the swelling process of the hydrogel, the flexible main chain gradually unfolds under the action of the swelling force, while the rigid short side chains form a mechanical interlocking structure and hinder the further sliding of the flexible main chain, ultimately achieving a swelling balance under the competition between the swelling force and the mechanical interlocking.

[0006] Furthermore, the hydrogel constructed based on the mechanical interlocking principle is characterized in that the flexible polymer main chain is a polymer chain generated by the addition polymerization of unsaturated small molecule monomers, and the rigid short side chains are single-end modified unsaturated bonds, polypeptides, proteins and other biological macromolecules.

[0007] Furthermore, the hydrogel constructed based on the principle of mechanical interlocking is characterized in that the flexible polymer main chain is polyacrylamide, poly N-hydroxymethyl acrylamide or poly (hydroxyethyl methacrylate) polymer; the rigid short side chain is (KA)3 (sequence is acrylic acid-tryptophan-glycine-glycine-lysine-alanine-lysine-alanine-lysine-alanine), K3A3 (sequence is acrylic acid-tryptophan-glycine-glycine-lysine-lysine-lysine-alanine-alanine-alanine), A3K3 (sequence is acrylic acid-tryptophan-glycine-glycine-alanine-alanine-alanine-lysine-lysine-lysine) or (KG)3 (sequence is acrylic acid-tryptophan-glycine-glycine-lysine-glycine-lysine-glycine-lysine-glycine-lysine-glycine).

[0008] A method for preparing a hydrogel based on the mechanical interlocking principle, characterized in that the unsaturated small molecule monomer constituting the main chain of the flexible polymer is acrylamide, and the rigid short side chain is (KA)3; the steps of preparing a super-strong, super-tough, crack-resistant hydrogel are as follows: the unsaturated small molecule monomer and a polypeptide or protein biomacromolecule with a single-end modified unsaturated bond are mixed and dissolved in a PBS buffer; the mixed solution is sonicated for 15 minutes to remove the dissolved oxygen therein; phenyl (2,4, 6-trimethylbenzoyl) lithium phosphate is used as a photoinitiator; the solution is then placed under 405nm blue light irradiation for 2 hours; the unsaturated small molecule monomers generate polymer chains through addition polymerization, and the polypeptide or protein biomacromolecules with single-end modified unsaturated bonds also randomly participate in the reaction and are connected to the polymer chains to obtain a primary hydrogel material; the obtained primary hydrogel material is immersed in 50 times the volume of PBS buffer for more than 24 hours to achieve the stability balance of the mechanical interlocking structure and the swelling of the hydrogel, thereby obtaining an ultra-strong, ultra-tough, crack-resistant hydrogel material.

[0009] Acrylamide was selected as a small molecule of a flexible main chain monomer and (KA)3 was selected as a rigid short side chain to prepare a hydrogel with super strength, super toughness and crack growth resistance. Acrylamide monomer and (KA)3 polypeptide were mixed and dissolved in PBS buffer (concentration of 0.01M, The mixed solution was sonicated for 15 minutes to remove dissolved oxygen therein; phenyl (2,4,6-trimethylbenzoyl) lithium phosphate was added to the sonicated solution at a final concentration of 0.0001 ml / ml as a photoinitiator; the solution was then placed under 405 nm blue light irradiation for 2 hours; acrylamide monomers were subjected to addition polymerization to generate polymer chains, and single-end acrylic acid-modified polypeptides (KA) 3 also randomly participated in the reaction and were connected to the polymer chains to obtain a primary hydrogel material; the obtained primary hydrogel material was immersed in 50 times the volume of PBS buffer for more than 24 hours to achieve the stability balance of the mechanical interlocking structure and the swelling of the hydrogel, thereby obtaining an ultra-strong, ultra-tough, crack-resistant hydrogel material.

[0010] Furthermore, the preparation method is characterized in that the PBS buffer concentration is 0.01M and the pH is 7.4.

[0011] An ultra-strong, ultra-tough, crack-growth-resistant hydrogel material for use in various types of flexible electronic devices.

[0012] An ultra-strong, ultra-tough, crack-growth-resistant hydrogel material for use in soft robotics.

[0013] A super strong, super tough, crack growth resistant hydrogel material for use in biomedicine, medical devices or tissue engineering.

[0014] The technical effects of the present invention are as follows: 1. Compared with traditional hydrogels, the hydrogel material in the present invention does not contain chemical crosslinking points or physical crosslinking points in the traditional sense, but is replaced by a mechanical interlocking structure between rigid chains. The new crosslinking mechanism realizes excellent mechanical properties in non-covalent hydrogels, with Young's modulus reaching 23kPa, breaking strength reaching 3.1MPa, and toughness reaching 28MJ / m 3 , fracture toughness reaches 57kJ / m 2 , the fracture toughness is 4 times that of rubber.

[0015] 2. Compared with the traditional hydrogel's ability to resist crack growth, the hydrogel material in the present invention has almost the same fracture strain as the crack-free hydrogel when the crack has 30% of the original width, and the crack insensitivity reaches 96%.

[0016] 5. Compared with traditional hydrogel materials, the hydrogel adhesive material of the present invention combines high toughness, high strength, and crack growth resistance, while traditional hydrogel materials can only achieve relatively high properties in one of the characteristics and it is difficult to achieve balanced properties in all aspects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the network of superstrong, supertough, and crack-growth-resistant hydrogel materials.

[0018] Figure 2 Comparison of missing rigid polypeptide side chains in superstrong, supertough, crack growth resistant hydrogel materials.

[0019] Figure 3 Characterization of mechanical properties of superstrong, supertough, and crack growth resistant hydrogel materials.

[0020] Figure 4 Photo of the crack growth resistance of super strong, super tough and crack growth resistant hydrogel material.

[0021] Figure 5 Testing the wear resistance of super strong, super tough, crack growth resistant hydrogel materials.

[0022] Figure 6 Characterization of the recovery mechanical properties of ultra-strong, ultra-tough, and crack growth-resistant hydrogel materials. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below with reference to the accompanying drawings.

[0024] A super-strong, super-tough, crack-resistant hydrogel material based on the principle of mechanical interlocking. The hydrogel network is mainly composed of flexible polymer main chains, and rigid short side chains are added to the flexible polymer chains as mechanical interlocking units. During the swelling process of the hydrogel, the flexible main chain gradually unfolds under the action of the swelling force, while the rigid short side chains form a mechanical interlocking structure and hinder the further sliding of the flexible main chain, eventually reaching a swelling balance under the competition between the swelling force and the mechanical interlocking ( Figure 1 ).

[0025] The flexible polymer main chain is a polymer chain generated by the addition polymerization of unsaturated small molecular monomers, and the preferred materials include: polyacrylamide, poly-N-hydroxymethyl acrylamide, poly-hydroxyethyl methacrylate and other polymers.

[0026] Taking acrylamide as a monomer small molecule to generate a flexible polymer main chain and (KA)3 as a typical example of a rigid short side chain, a super strong, super tough, and crack growth resistant hydrogel was prepared; acrylamide monomer and (KA)3 polypeptide were mixed and dissolved in PBS buffer (concentration of 0.01M, The mixed solution was ultrasonicated for 15 minutes to remove the dissolved oxygen therein; phenyl (2,4,6-trimethylbenzoyl) lithium phosphate was added to the ultrasonicated solution at a final concentration of 0.0001 ml / ml as a photoinitiator; the solution was then placed under 405 nm blue light irradiation for 2 hours; acrylamide monomers were subjected to addition polymerization to generate polymer chains, polyacrylamide (PAM), and single-end acrylic acid-modified polypeptides (KA) 3 also randomly participated in the reaction and were connected to the polymer chains to obtain primary hydrogel materials; the obtained primary hydrogel materials were immersed in 50 times the volume of PBS buffer for more than 24 hours to complete the stability balance of the mechanical interlocking structure and the swelling of the hydrogel, and obtain super-strong, super-tough, and crack-resistant hydrogel materials. Among them, the concentration of PBS buffer was 0.01 M and the pH was 7.4.

[0027] The following are examples of testing the various properties of the present invention.

[0028] Example 1 Verification of the stability of the hydrogel constructed with the mechanical interlocking structure in the present invention In the present invention, in order to verify the effect of rigid short side chains on the stability of the mechanical interlocking structure, a control group experiment was designed: the (KA)3 polypeptide in the hydrogel raw material of the experimental group was replaced with an equal molar amount of acrylamide as the control group, and the rest of the hydrogel preparation method remained unchanged. The results showed that after 24 hours of swelling, the control group hydrogel could not support a fixed shape and was in the form of a viscous droplet, while the experimental group hydrogel maintained a stable round shape and was transparent and elastic (such as Figure 2 as shown).

[0029] Example 2 Mechanical testing of strength and toughness of the hydrogel material of the present invention In order to verify the strength and toughness of the hydrogel material in the present invention, the material was subjected to standard mechanical property tests, and different flexible main chain monomers and rigid short side chains were used as control groups. Figure 3 As shown in a, the monomers constituting the flexible polymer main chain are acrylamide, N-hydroxymethyl acrylamide, and hydroxyethyl methacrylate, and the rigid short side chain polypeptides are (KA)3, K3A3, A3K3, and (KG)3. Among them, the PAM-(KA)3 combination has the best mechanical properties, with a tensile breaking strain of 26mm / mm, a Young's modulus of 23kPa, a breaking strength of 3.1MPa, and a toughness of 28MJ / m 3 , fracture toughness reaches 57kJ / m 2, the fracture toughness is 4 times that of rubber. Figure 3 As shown in Figure b, the mechanical properties of this hydrogel material vary with the polypeptide content in the hydrogel network, and the optimal mechanical properties can be obtained when the molar ratio of polypeptide to acrylamide monomer is 0.032. Figure 3 As shown in c, in the tensile comparison test of hydrogels with and without cracks, both have almost the same fracture strain. Figure 4 Two hydrogel photos with the same tensile fracture strain are shown, which demonstrates the excellent crack growth resistance of the hydrogel material of the present invention.

[0030] Example 3 Testing of the friction resistance of the hydrogel material of the present invention.

[0031] In order to further verify the anti-crack growth performance of the hydrogel material in the present invention, the hydrogel material in the present invention and other experimental groups were subjected to the same friction resistance test. Figure 5 a shows the test method, using the CS mode of the rheometer with a torque of 2525 μNm, a normal force of 5 N, and an angular velocity of 1 rad / s. Figure 5 a. A sudden change in strain of PAM-K3A3 hydrogel was observed at 0.5 h, indicating that tiny cracks inside the hydrogel grew rapidly under cyclic shear force at this time. The mutation of ordinary BIS hydrogel occurred at 5.58 h, indicating that its wear resistance was slightly better than that of PAM-K3A3 hydrogel. The strain of PAM-(KA)3 hydrogel remained stable within 6 h, indicating that it has excellent wear resistance. Commercial Teflon was tested as a control group. Figure 5 b shows the photo of the hydrogels after the friction test. The PAM-(KA)3 hydrogel remained basically intact, while the PAM-K3A3 hydrogel and the ordinary BIS hydrogel were damaged.

[0032] Example 4 Rapid mechanical property recovery test of the hydrogel material of the present invention.

[0033] In order to further verify the anti-crack growth performance of the hydrogel material in the present invention, the hydrogel material was subjected to a continuous stretching mechanical test, wherein the maximum strain of the continuous stretching was 8 mm / mm and the stretching rate was 10 mm / min. Figure 6 It shows that after 1000 continuous stretching cycles, its maximum stress remains at 96.2%, which demonstrates its excellent resistance to crack growth inside the hydrogel.

Claims

1. A hydrogel constructed based on the principle of mechanical interlocking, characterized in that: The hydrogel is composed of a flexible polymer main chain and rigid short side chains, wherein the flexible polymer main chain is wound as the main body, and rigid short side chains are added to the flexible polymer chain as mechanical interlocking constituent units.

2. The hydrogel constructed based on the mechanical interlocking principle according to claim 1, characterized in that: The flexible polymer main chain is a polymer chain generated by the addition polymerization of unsaturated small molecule monomers, and the rigid short side chain is a polypeptide or protein biomacromolecule with a single end modified with an unsaturated bond.

3. The hydrogel constructed based on the mechanical interlocking principle according to claim 1, characterized in that: The flexible polymer main chain is polyacrylamide, poly N-hydroxymethyl acrylamide or poly hydroxyethyl methacrylate polymer; the rigid short side chain is (KA)3 (sequence is acrylic acid-tryptophan-glycine-glycine-lysine-alanine-lysine-alanine-lysine-alanine), K3A3 (sequence is acrylic acid-tryptophan-glycine-glycine-lysine-lysine-lysine-alanine-alanine-alanine), A3K3 (sequence is acrylic acid-tryptophan-glycine-glycine-alanine-alanine-alanine-lysine-lysine-lysine) or (KG)3 (sequence is acrylic acid-tryptophan-glycine-glycine-lysine-glycine-lysine-glycine-lysine-glycine-lysine-glycine).

4. A method for preparing a hydrogel based on the mechanical interlocking principle according to claim 1, characterized in that: The unsaturated small molecule monomer constituting the main chain of the flexible polymer is acrylamide, and the rigid short side chain is (KA)3; the steps of preparing a super-strong, super-tough and crack-resistant hydrogel are as follows: the unsaturated small molecule monomer and a polypeptide or protein biomacromolecule with a single-end modified unsaturated bond are mixed and dissolved in a PBS buffer solution; the mixed solution is ultrasonicated for 15 minutes to remove the dissolved oxygen therein; phenyl (2,4,6-trimethylbenzoyl) lithium phosphate with a final concentration of 0.0001 ml / ml is added to the solution after ultrasonication as a photoinitiator; then the solution is placed under 405nm blue light irradiation for 2 hours; the unsaturated small molecule monomer generates a polymer chain through addition polymerization, and the polypeptide or protein biomacromolecule with a single-end modified unsaturated bond also randomly participates in the reaction and is connected to the polymer chain to obtain a primary hydrogel material; the obtained primary hydrogel material is immersed in a 50-fold volume of PBS buffer solution for more than 24 hours to complete the stability balance of the mechanical interlocking structure and the swelling of the hydrogel, so as to obtain a super-strong, super-tough and crack-resistant hydrogel material.

5. The preparation method according to claim 4, characterized in that: The concentration of PBS buffer is 0.01 M and the pH is 7.

4.

6. Application of the hydrogel constructed based on the mechanical interlocking principle as claimed in claim 1 in various flexible electronic devices.

7. An application of the hydrogel constructed based on the mechanical interlocking principle as claimed in claim 1 in soft robots.

8. An application of the hydrogel constructed based on the mechanical interlocking principle as claimed in claim 1 in biomedicine, medical devices or tissue engineering.

Citation Information

Patent Citations

  • Novel gradient hydrogel material, and preparation method and application thereof

    CN112126083A

  • High-toughness hydrogel based on amino acid acrylamide derivative and preparation method of high-toughness hydrogel

    CN112142911A

  • Super-strong, super-tough, quick-recovery and anti-fatigue hydrogel material as well as preparation method and application thereof

    CN116217837A

  • Hydrogels having enhanced elasticity and mechanical strength properties

    US20030232895A1